International Debt for the Sake of Local Debt and The Economic Situation in Iraq - Hawre Latif Majeed (Eurasian Journal of Management & Social Sciences, 2022)
This study objectively examines the influence of Iraq's foreign debt on its economy. Periodic secondary data were obtained (2004 -2021). Descriptive statistics were used to analyze the data collected for the investigation. Multiple regression analyses were done to examine the data's causation effect link. It employed foreign debt as the dependent variable. In contrast, gross domestic product, total government expenditures, and total government debt were the independent variables, and gross international reserves were used as indices for the independent variable. This study explains why economics in developing countries such as Iraq suffers in management because the government depends on external debt to supply revenues for the total government expenditures. At the same time, the international reserves of Iraq are insignificant in explaining economic growth. The study recommends, amongst other things, that good change in the use of foreign loans on investment expenditure will be stimulated to stimulate the Iraqi economy. The results indicate that external debt significantly negatively affects the gross domestic product.